KUALITAS AUDIT MELALUI ANALISIS FAKTOR- FAKTOR INDEPENDENSI DAN PROFESIONALISME AUDIT INTERNAL - Ari Bramasto; Sri Dewi Anggadini; Asri Syahriani (STIE Muhammadiyah Jakarta, 2021)
ABSTRACTAudit quality is the accuracy of information reported by the auditor in accordance with the auditing standards used by the auditor including information on accounting violations in the company's financial reports, for that the role of the internal auditor is important for the sustainability of the company, where its role is to provide continuous supervision and assessment, the resulting audit quality depends of the independence and professionalism of the auditors themselves. This study aims to determine how much influence the independence of Internal Audit on audit quality and how much influence the professionalism of internal auditors on audit quality at PT Foximas Mandiri Bandung.The method used in this research is descriptive and verification methods. The population in this study were employees of PT Foximas Mandiri Bandung. Sampling was done using the Census Technique, with a sample of 26 respondents. The type of data used in this study is primary data. The data collection technique used statistical test modeling using the SPSS V.22 program.The results of this study indicate that: 1) The independence of the Internal Audit has an effect on audit quality, the internal auditors are free from pressure or managerial intervention and avoiding the use of unclear language in the audit report being the factor with the lowest gap, namely 9.23% 2) Professionalism of Internal Audit influence on audit quality, confidence in perophysical regulations is the factor with the lowest gap, namely 1.54% .